Analisis Perubahan Penggunaan Lahan Dan Prediksinya dengan Menggunakan Markov – Cellular Automata Di Wilayah Peri Urban Kota Malang - Mirza Permana; Santun Risma Pandopatan Sitorus; Darmawan Darmawan (Diponegoro University, 2021)
Peri Urban Area is a unique region with spatial dynamics that continues to experience changes that have an important role to play in the urban life in the future. There are 8 sub-districts in Malang Regency which are directly adjacent to Malang City and have a significant influence on the development of the city. Objectives of this research are to determine the dynamics of land use change from 2008 - 2018 and to predict land use in 2030. The method used is the analysis of land use changes from landsat TM 8 images in 2008 and 2013 to predict land use in 2018 which then tested the validity to get a level of accuracy. The results showed the development of built-up area has increased by 12% while agricultural land has experienced a declining trend. Significant changes occurred in Singosari, Pakisaji and Karangploso sub-district. Validation of land use between the predictions of 2018 and actual land use in 2018 showed that the value of kappa was quite high, at 87%. The trend of land use in peri-urban areas until the year 2030 is predicted to have built up area of 26,456 ha, which means an increase 17,686 ha (33.6%) from the existing year 2018. The potential incompatibility of the RTRW with the predicted land use in 2030 is 11,950 ha or 22.7%.